UV-ANALYTICAL METHOD DEVELOPMENT AND VALIDATION FOR SIMULTANEOUS ESTIMATION OF DAPOXETINE HYDROCHLORIDE AND SILDENAFIL CITRATE IN TABLET DOSAGE FORM - Gadiya, Hemesh; Maheshwari, Monika; Dashora, Ashok (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this research was to develop and validate a simple ultraviolet (UV) spectrophotometric method for simultaneous determination of sildenafil citrate and dapoxetine hydrochloride in a pharmaceutical formulation. Methods: Two simple UV spectrophotometric methods have been developed for simultaneous determination of sildenafil citrate and dapoxetine hydrochloride. For both methods, stock solutions were prepared in methanol followed by the further required dilutions with methanol. Proposed dual-wavelength method and ratio derivative method, the wavelength of maximum absorption for sildenafil citrate and dapoxetine hydrochloride was 292 nm and 231 nm, respectively. Results: In both methods, the linearity range lies between 10 and 60 μg/ml for sildenafil citrate and 2–12 μg/mL for dapoxetine hydrochloride with their respective wavelengths. By dual-wavelength method, the percentage of sildenafil citrate and dapoxetine hydrochloride was found to be 101.3% and 100.3%, respectively. Conclusion: Result obtained in this research work clearly indicated that both these methods were found to be accurate, precise, stable, and robust as indicated by low values of percentage relative standard deviation. Thus, the present study gives an excellent method for the determination of both the drugs in combined tablet formulation.